PENGARUH ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP NILAI PERUSAHAAN MELALUI RETURN SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN PERIODE 2015-2019 - Nurbaya Mahasari Sella; Sugiarti Binastuti (Jurnal Ilmiah Raflesia Akuntansi, 2021)
Abstract - his study aims to see the effect of Eva and Mva on firm value through stock returns as an intervening variable for manufacturing companies in the food and beverage sub-sector for the 2015-2019 period.This study uses quantitative data types with secondary data sources. Sample selection using purposive sampling method obtained from the annual financial statements through the official website of each company and www.idx.co.id. The variable used is Economic Value Added which is measured by subtracting the results of nopat and capital charges. Market Value Added as measured by company value and invested capital. Stock Return is measured by the previous share price and current share price and Company Value is obtained by the share price, outstanding shares, total assets and total liabilities. The results of the regression analysis show that partially economic value added and stock returns have no effect on firm value, while market value added variables affect firm value. Simultaneously the variables of economic value added, market value added and stock returns simultaneously affect the value of the company. The path analysis shows that there is a direct effect with positive results on the variables eva and mva on firm value through stock returns as an intervening variable.